Designing 'Matcuher' android-based learning media integrating the sedekah bumi tradition to support students’ critical thinking skills - Muhtarom, Muhtarom; Masayu Amalia, Yulianti; Rejeki, Sri (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to develop and evaluate the potential of 'Matcuher,' an Android-based learning media integrating the local Sedekah Bumi tradition, to support students' critical thinking skills in curved-surface solids. Method: Employing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, this Research and Development (R&D) study utilised a one-group pretest-posttest design. The participants were 33 ninth-grade students in Semarang City, selected through convenience sampling. Data were collected through expert validation sheets, an empirically validated critical-thinking test, and student response questionnaires. Findings: The results indicate that Matcuher media was rated highly valid and feasible across both the material and design aspects. It also showed potential to enhance students’ critical thinking skills and received positive feedback. Following the intervention, students showed a preliminary improvement in critical thinking, with a paired-samples t-test indicating significant differences and an N-Gain score of 0.59 (moderate improvement). Matcuher provides an interactive learning experience by transforming cultural elements into formal mathematical models. Students also responded positively to the media's practicality. Significance: Matcuher media on curved-surface solid geometry using the Ethno-RME approach proved to be valid, practical, and effective in enhancing students’ critical thinking skills.